2022
DOI: 10.1017/s0022278x22000210
|View full text |Cite
|
Sign up to set email alerts
|

Researching Africa and the offshore world

Abstract: One of the key features of today's global economy is an ‘offshore world’ of financial structures, institutions and techniques designed to provide secrecy, asset protection and tax exemption. While its worldwide impact is very significant, Africa is affected to an unusual extent by the strategies of tax avoidance/evasion, outward financial flows (both legal and illegal) and corruption enabled by the offshore world. This is corroborated by a number of quantitative studies of capital flight as well as by influent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…In this paper, we build upon our identification of these increasingly influential ‘Transnational Uncivil Society Networks’ (TUSNs) to analyse the shifts currently underway in the ecology of globalization. Advancing from findings from our research on Eurasia and Africa (Cooley and Heathershaw, 2017; Soares de Oliveira, 2015, 2022), we argue that these strategies of reputation-laundering are neither illicit nor marginal, but very much a product of the actors, institutions and markets generated by the liberal international order. We also explore TUSNs empirically in their Eurasian and African forms, noting regional variations in common themes of global networking and reputation-laundering.…”
Section: Introductionmentioning
confidence: 58%
“…In this paper, we build upon our identification of these increasingly influential ‘Transnational Uncivil Society Networks’ (TUSNs) to analyse the shifts currently underway in the ecology of globalization. Advancing from findings from our research on Eurasia and Africa (Cooley and Heathershaw, 2017; Soares de Oliveira, 2015, 2022), we argue that these strategies of reputation-laundering are neither illicit nor marginal, but very much a product of the actors, institutions and markets generated by the liberal international order. We also explore TUSNs empirically in their Eurasian and African forms, noting regional variations in common themes of global networking and reputation-laundering.…”
Section: Introductionmentioning
confidence: 58%
“…The framework for taxing the profits of international business has been in place for 100 years. Decolonisation was accompanied by the movement of wealth and assets offshore, and former colonial powers strategically supported dependent states to set up low or zero tax regimes with little regulation for non-residents, both companies and individuals [82,83]. During the mid-twentieth century, efforts by the United Nations to work on reforming international tax and transnational corporations faltered, and the forum shifted to less inclusive spaces, primarily the OECD [84].…”
Section: The Way Forward Internationalmentioning
confidence: 99%
“…The bank's collapse was precipitated by a massive money laundering scandal that obviously implicated its largest depositor, Obiang, and publicly exposed his family's network of assets in the U.S. It was widely reported that Obiang's account held up to $700 million, deposited in many instances in suitcases of 100$ bills (U.S. Congress, 2004, p. 165;Oliveira, 2022).…”
Section: Corporate and Soft Powermentioning
confidence: 99%